2016
DOI: 10.1111/hel.12333
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic of Helicobacter pylori infection

Abstract: There is progress in endoscopy techniques. While it is not yet possible to detect Helicobacter pylori directly in the stomach, it becomes easier to detect the mucosal changes induced by the bacteria. Some small changes can also increase the sensitivity of the invasive tests, for example culture or histology, but the wide use of proton-pump inhibitors has a negative impact on these tests. Only molecular methods are able to detect a limited load of bacteria, especially by using real-time PCR but also with new me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
1
20
0
2
Order By: Relevance
“…Diagnosis, preferably made at the primary care level, points to the use of fecal antigen testing because of its ability to detect minimal quantities of antigen in stool samples (~ng/mL), and the clinic approach conveniently shifts most of the onus of Using a new monoclonal antibody sandwich method and chemiluminescent immunoassay technology, this study assessed 277 subjects in the United States and Europe, of which 24.2% were determined to have active H. pylori infection by CRM. The study showed a sensitivity of 95.5% (95% CI: 87.5-99.1%) and a specificity of 97.6% (95% CI: 94.5-99.2%), and the performance was comparable to a study performed in Europe using a previous version of the LIAISON kit that used different antibodies in the assay setup [27]. The current results also compare favorably with other widely marketed stool antigen tests.…”
Section: Discussionsupporting
confidence: 73%
“…Diagnosis, preferably made at the primary care level, points to the use of fecal antigen testing because of its ability to detect minimal quantities of antigen in stool samples (~ng/mL), and the clinic approach conveniently shifts most of the onus of Using a new monoclonal antibody sandwich method and chemiluminescent immunoassay technology, this study assessed 277 subjects in the United States and Europe, of which 24.2% were determined to have active H. pylori infection by CRM. The study showed a sensitivity of 95.5% (95% CI: 87.5-99.1%) and a specificity of 97.6% (95% CI: 94.5-99.2%), and the performance was comparable to a study performed in Europe using a previous version of the LIAISON kit that used different antibodies in the assay setup [27]. The current results also compare favorably with other widely marketed stool antigen tests.…”
Section: Discussionsupporting
confidence: 73%
“…Helicobacter pylori ( H. pylori ), one of the most common chronic infections, can lead to chronic gastritis, gastric and duodenal ulcers and sometimes gastric lymphoma and adenocarcinoma ( 1 3 ). Colonization is usually lifelong without treatment, and its prevalence varies from 20% to 50% in developed countries to more than 80% in resource limited countries ( 4 6 ). The definitive diagnosis of H. pylori is isolation of the microbe or its detection in histology of gastric biopsy by endoscopy, which are expensive and invasive tests ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even today, medical devices designed to detect breath ammonia originally produced in the stomach are in use clinically to detect infection with the Gram negative bacterium, Helicobacter pylori, an important human pathogen that despite a decline in prevalence still infects approximately 50% of humans worldwide. H. pylori infection is the most common causative agent of gastritis, peptic ulcers and gastric cancer [2] . The presence of urease in the stomach was discovered early in the 20th century (reviewed in [1] and [3] ).…”
Section: Introductionmentioning
confidence: 99%